Inhibition of the NOD-Like Receptor Protein 3 Inflammasome Is Protective in Juvenile Influenza A Virus Infection - Coates, Bria M.; Staricha, Kelly L.; Ravindran, Nandini; Koch, Clarissa M.; Cheng, Yuan; Davis, Jennifer M.; Shumaker, Dale K.; Ridge, Karen M. (Frontiers in Immunology, 2017)
Influenza A virus (IAV) is a significant cause of life-threatening lower respiratory tract infections in children. Antiviral therapy is the mainstay of treatment, but its effectiveness in this age group has been questioned. In addition, damage inflicted on the lungs by the immune response to the virus may be as important to the development of severe lung injury during IAV infection as the cytotoxic effects of the virus itself. A crucial step in the immune response to IAV is activation of the NLRP3 inflammasome and the subsequent secretion of the inflammatory cytokines, interleukin 1β (IL-1β) and IL-18. The IAV matrix 2 proton channel (M2) has been shown to be an important activator of the NLRP3 inflammasome during IAV infection. We sought to interrupt this ion channel-mediated activation of the NLRP3 inflammasome through inhibition of NLRP3 or the cytokine downstream from its activation, IL-1β. Using our juvenile mouse model of IAV infection, we show that inhibition of the NLRP3 inflammasome with the small molecule inhibitor, MCC950, beginning 3 days after infection with IAV, improves survival in juvenile mice. Treatment with MCC950 reduces NLRP3 levels in lung homogenates, decreases IL-18 secretion into the alveolar space, and inhibits NLRP3 inflammasome activation in alveolar macrophages. Importantly, inhibition of the NLRP3 inflammasome with MCC950 does not impair viral clearance. In contrast, inhibition of IL-1β signaling with the IL-1 receptor antagonist, anakinra, is insufficient to protect juvenile mice from IAV. Our findings suggest that targeting the NLRP3 inflammasome in juvenile IAV infection may improve disease outcomes in this age group.